Liability rules can rationalize greater victim vulnerability. Issue 21 (15th December 2021) - Friehe, Tim; Tabbach, Avraham
ABSTRACT: This paper shows that an imperfect strict liability rule can induce victims to increase the losses they incur in the event of an accident, and that similar incentives exist under the negligence rule. Using a simple model in which victims can influence their harm distribution, we identify two potential reasons why victims may benefit from greater 'vulnerability', namely strategic effects on own future and others' behaviour.